Diode laser and periodontal regeneration-assisted management of implant complications in anterior maxilla - Sanjeev Kumar Salaria; Isha Sharma; Navjot Kaur Brar; Satwant Kaur (Wolters Kluwer Medknow Publications, 2018)
Dental implant is being considered successful if the patient is pleased with both of its functional and esthetic outcome. As implant complications (such as peri-implantitis, inappropriate implant position, wrong angulation, and implant location too close to anatomical structures) have been frequently encountered in dental practice, therefore, thorough knowledge to manage such complications is the key prerequisite to prevent the failure of implant. The present case report discussed the etiology, diagnosis of early peri-implantitis, and periodontal abscess with their successful management through periodontal regeneration and diode laser-assisted therapy.